2021
DOI: 10.1176/appi.prcp.20210022
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to aid self‐isolation and quarantine for individuals with severe and persistent mental illness during the COVID‐19 pandemic: A systematic review

Abstract: Background Individuals with severe and persistent mental illness (SPMI) have a higher risk of contracting COVID‐19 than individuals without SPMI. In combination with physical distancing, hygiene protocols, and vaccines, quarantine and self‐isolation are primary means of viral containment. However, individuals with SPMI may experience more difficulties with mandated quarantine or self‐isolation because of their illness(es), stigma, and marginalization. To date, there is a lack of consensus on strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Preliminary scoping searches identified three reviews that were relevant to this review question: two rapid reviews (Cardwell et al 2022, Patel et al 2021) and one systematic review (Bahji et al 2021). A summary of the included reviews is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary scoping searches identified three reviews that were relevant to this review question: two rapid reviews (Cardwell et al 2022, Patel et al 2021) and one systematic review (Bahji et al 2021). A summary of the included reviews is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Patel et al (2021) evaluated the effectiveness of financial support interventions and reported on two studies (Bodas & Peleg 2020, Pichler et al 2020). The third review by Bahji et al (2021) aimed to evaluate strategies to aid self-isolation and quarantine for individuals with severe and persistent mental illness during the COVID-19 pandemic, and included one relevant study (Fuchs et al 2021). All five studies identified by these reviews were unique, and no studies overlapped between the reviews.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one study suggested that identifying patients seen in consultation by ACS using hospital records can be obscured by a lack of reliable diagnostic or procedural codes 81 . Finally, in the context of COVID-19, there is a need to explore alternative models (eg, virtual care platforms) to provide ACS amid pandemic-related service disruptions 82–84 …”
Section: Discussionmentioning
confidence: 99%
“…81 Finally, in the context of COVID-19, there is a need to explore alternative models (eg, virtual care platforms) to provide ACS amid pandemic-related service disruptions. [82][83][84]…”
Section: Implications For Practice Policy and Future Researchmentioning
confidence: 99%
“…As a consequence, vulnerable populations have been disproportionately afflicted in the COVID-19 era [ 9 ]. People suffering from a mental health disorder or disability [ 10 , 11 ], those who are educationally or economically disadvantaged, racial and ethnic minorities, refugees, migrants [ 12 ], the homeless, minors, and the elderly are among those adversely affected. Additionally, nontraditional cases are seeking psychosocial counselling, including employed parents as well as school and university students.…”
mentioning
confidence: 99%